A VHDL Architecture for Auto Encrypting SD Cards - Davidsson, Alexander; Rasmusson, Torbjörn (My University, 2016)
This thesis details the design of an encrypted SD-card adapter for journalists to be used in destabilized areas. The SD-card adapter should be designed to protect the journalist's photographs while allowing previewing of the photograph until the SD-card is powered down. The SD-card adapter is designed to appear as a generic SD-card adapter with the exception that it encrypts the data and hides any changes in the le system. The design is based around a FPGA with use of a publicly available IP-core for encryption. The SD-card adapter uses both symmetrical and asymmetrical encryption for protection of individual les. A soft-core is used for generating encryption keys, asymmetrical encryption and general management. Through use of software based emulation, the concept was proven feasible.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science